Hubungan Fear Of Missing Out dengan Impulsive Buying pada Penggemar Kpop Generasi Z - Adheline, Nofrilia Getza; Suhesty, Aulia (Universitas Muhammadiyah Metro, 2025)
The phenomenon that is rampant now is that k-pop fans feel satisfied with themselves when they get the idol merchandise they want from excessive shopping This study aims to determine the relationship between fear of missing out and impulsive buying in generation z kpop fans. This research uses a quantitative approach. The research subjects were 100 generation z kpop fans selected using non-probability sampling technique. The data analysis technique used is correlation. The collected data were analyzed with the help of the Statistical Package For Social Science (SPSS) version 25 for windows program. The results showed that there was a positive correlation between the fear of missing out variable and impulsive buying showing R count of 0.718> R table of 0.197 with a p value of 0.000 (p <0.05).